Safety evaluation of an extension of use of the food enzyme pectinesterase from the genetically modified Trichoderma reesei strain RF6201 - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme pectinesterase (pectin pectylhydrolase, EC 3.1.1.11) is produced with the genetically modified Trichoderma reesei strain RF6201 by AB Enzymes GmbH. A safety evaluation of this food enzyme was made previously, in which EFSA concluded that this food enzyme did not give rise to safety concerns when used in five food manufacturing processes. Subsequently, the applicant has requested to extend its use to include two additional processes. In this assessment, EFSA updated the safety evaluation of this food enzyme when used in a total of seven food manufacturing processes. As the food enzyme–total organic solids (TOS) are removed from or not carried into the final foods in three food manufacturing processes, the dietary exposure to the food enzyme–TOS was estimated only for the remaining four processes. The dietary exposure was calculated to be up to 0.488 mg TOS/kg body weight (bw) per day in European populations. When combined with the no observed adverse effect level previously reported (1000 mg TOS/kg bw per day, the highest dose tested), the Panel derived a margin of exposure of at least 2049. Based on the new data, the revised margin of exposure and the previous evaluation, the Panel concluded that this food enzyme does not give rise to safety concerns under the revised intended conditions of use.